Containing systemic risk - Karl Whelan (University College Dublin, UCD School of Economics, 2009)
Systemic risk refers to the risk of financial system breakdown due to linkages between institutions. This risk cannot be assessed by looking at how individual institutions manage risks but instead requires a full understanding of how the system as a whole operates. At present, the data available to central banks and financial regulators are not at all adequate for the task of assessing systemic risk and the new European Systemic Risk Board needs to address this issue. There is a lot of exciting ongoing research devoted to measuring systemic risk and providing signals to regulators as to when and where they should intervene. However, the tools being developed are still limited in their usefulness. More pressing than the development of these tools is the development and implementation of policy measures to make the financial system more robust. These measures should include higher capital ratios, limits on non-core funding and redesigning financial systems to be less complex.
hdl:10197/2625
Keywords: 330